Characteristic study of palm oil mill effluent crystals - Ngatiman, Muzzammil; Jami, Mohammed Saedi; Abu Bakar, Mohd Rushdi; Subramaniam, Vijaya; Loh, Soh Kheang (2016)
The formation of crystals in palm oil mill effluent (POME) occurs as early as in the secondary stage of POME treatment pond system. It continues to form in the subsequent tertiary treatment process leading to inefficient treatment process. Reduced piping diameter, clogging of crystal debris and leakages are among the main problems caused by crystal formation. The occurrence of POME crystal in the palm oil milling process is rarely reported in scientific article even though it is a common problem faced by the palm oil industry when it comes to POME management. The crystal samples were characterized by energy dispersive spectroscopy (EDS), scanning electron microscopy (SEM), thermo gravimetric analysis (TGA) and X-ray Diffraction (XRD). The results showed that the crystals formed were mainly struvite-a phosphate mineral with formula NH₄MgPO₄·6H₂O oforthorhombic crystallization system. The crystals consisted of mainly inorganic matters i.e. ash content as high as 49.2 wt%, carbon (C) and hydrogen (H) contents less than 5 wt%. Its significant composition of phosphorous up to 22 wt% proved its potential as an alternative source to the ever-increasing demand of phosphate forfertilization with lesser environmental impact.